If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 2 = -12 + 12x Combine like terms: -4 + 2 = -2 -2 = -12 + 12x Solving -2 = -12 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -2 + -12x = -12 + 12x + -12x Combine like terms: 12x + -12x = 0 -2 + -12x = -12 + 0 -2 + -12x = -12 Add '2' to each side of the equation. -2 + 2 + -12x = -12 + 2 Combine like terms: -2 + 2 = 0 0 + -12x = -12 + 2 -12x = -12 + 2 Combine like terms: -12 + 2 = -10 -12x = -10 Divide each side by '-12'. x = 0.8333333333 Simplifying x = 0.8333333333
| 7p-(3p+4)=-2(2p+1)+10 | | 9-2x=2x+9 | | -2z+4(z-7)=9z+7(-2+z) | | 5/7x3/4= | | x+(x*0.1957)+64.84=400 | | -7.5x=-6.666 | | -46+6x=104+12x | | Y/3-13=-11 | | x+19=376 | | 7x+-2y+16w+-5y+-6w+8x= | | 25g-200=25 | | ln(8x-5)=4 | | 5p-5=6p+9 | | X-y+50=0 | | 5(2+3x)=15x+10 | | 9x-.85=8x+1.14 | | 2sin(x+40)=3cos(x-10) | | 7x+6=-4+2x+25 | | (2x+36)+(x-12)+(x)=180 | | 7x+6=4x+7.5 | | (Y-9)(3+12)= | | 9v=u | | (15a^2)-3a=3-7a | | 12x+7=11x+8 | | 6+4y=12-2y | | 4(y+9)-3y=45 | | c+11=-30 | | 5x+11=3x+9 | | 12-10x+11x=6 | | n-m=14 | | 5x-2+x=3x-4-5 | | 5x-2-4x=1-11 |